A Notable Prevalence of HIV-Associated Stroke in an Endemic Region. (30th August 2022) - Zimba, Stanley; Benjamin, Laura
Abstract : Low- and middle-income countries shoulder a disproportionate burden of HIV infection, which frequently intertwines with a high prevalence of noncommunicable diseases such as stroke. Sub-Saharan Africa, for example, has 12% of the world population but 71% of HIV infections worldwide, and the prevalence of patients with stroke and coexisting HIV infection has risen. 1 This is supported by data from the USA, which shows that admissions of patients with stroke and concurrent HIV infection have increased by 43% over 9 years. 2 Furthermore, people living with HIV (PLWH) are twice as likely to develop cardiovascular disease, and the global burden of HIV-associated cardiovascular disease has tripled over the past 2 decades. 3 HIV is now responsible for 2.6 million cardiovascular disease–associated disability-adjusted life years per year, with the greatest effect in sub-Saharan Africa. This increase has occurred despite good antiretroviral therapy (ART) uptake. Despite this compelling evidence, the national stroke guidance in the continent of Africa makes no mention of HIV. 4 Burden assessments, including incidence, prevalence, risk attribution, risk reduction, mortality, and disability rates of HIV-associated stroke in HIV endemic populations at a national, regional, and continental level, are lacking and would help drive the agenda forward. Although we have increasing certainty about the etiologic role of HIV infection in stroke and our knowledge about the multifactorial mechanisms is improving, disproportionately few research articles are emerging from the regions most affected by HIV infection, limiting progress.